Future Prospects of University Students Studying Psychological Counselling and Guidance: A Case Study - Birgül ULUTAŞ; Emre GÜNEY (Anı Publishing, 2021)
Dramatic increases in the unemployment rates worldwide have been observed for the last two decades. The number of unemployed individuals, which was 800 million in 1995, has exceeded one billion at the beginning of the 21st century and while the rates of unemployment have long been one of the primary agendas of the governments, they are continuing to rise irrevocably. Presenting the expectations and worries of prospective teachers studying at the Department of Guidance and Psychological Counselling (GPC) to raise the visibility of an important problem in the field of raising teachers and employment policies is the main objective of this research. In this research based on a case study, which is a qualitative research pattern, the data were collected using semi-structured interview questions to the participants composed of eight female and eight male students from different stages. The findings obtained in this study showed that the majority of the students, especially the students from low-income families, based their future expectations on governmental teacher appointments and they attached considerable importance to KPSS (PPSE, Public Personnel Selection Examination). Moreover, a majority of students felt obliged to start working as early as possible and as a result, they delayed their plans, such as pursuing a Master's degree. Also, a secure employment condition was their biggest expectation for the future and they did not have any hopes for higher standards of living conditions. Making the content of the GPC teachers' written examination for an appointment more fitting to their field of expertise, a more objective interviewing process, and annulling the appointments of teachers out of the GPC field are among the proposals of this research.